2017
DOI: 10.1161/circoutcomes.116.003310
|View full text |Cite
|
Sign up to set email alerts
|

Use of Mixed Methods Research in Research on Coronary Artery Disease, Diabetes Mellitus, and Hypertension

Abstract: Background-Mixed methods research, the use of both qualitative and quantitative methods within 1 program of study, is becoming increasingly popular to allow investigators to explore patient experiences (qualitative) and also measure outcomes (quantitative). Coronary artery disease and its risk factors are some of the most studied conditions; however, the extent to which mixed methods studies are being conducted in these content areas is unknown. We sought to comprehensively describe the characteristics of publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…In line with findings reported in recent reviews [8,26,34], many articles reported a convergent design and cited complementarity as the main rationale for mixing methods. In these studies, the findings of the quantitative and the qualitative components were used to enrich or elaborate on the findings of the other component or to provide further insights.…”
Section: Main Findingssupporting
confidence: 79%
“…In line with findings reported in recent reviews [8,26,34], many articles reported a convergent design and cited complementarity as the main rationale for mixing methods. In these studies, the findings of the quantitative and the qualitative components were used to enrich or elaborate on the findings of the other component or to provide further insights.…”
Section: Main Findingssupporting
confidence: 79%
“…Epidemiologic research has revealed that alcohol consumption is related to the risk of CHD incidence ( 33 ). Besides, diabetes and hypertension are the major risk factors for CHD incidence ( 34 ). However, no association was observed in drinkers and in CHD patients with diabetes or hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…The strengths of our study are that we captured the experiences and preferences for hypertension management and potential usefulness of a mHealth or eHealth intervention among Black and Latinx populations. Few studies have applied mixed-methods to explore both medication adherence and the use of technology for managing hypertension [ 21 , 22 ]. Using a mixed-methods study design we elicited greater insights to medication adherence practices and interest in technology for a behavioral intervention, than using only quantitative methods.…”
Section: Discussionmentioning
confidence: 99%